The Public Accountant Firm affiliated with Big Four Firm, Auditor Industry Specialiation, Auditor Opinion influence Earnings Management - Frisdiantara, Christea; Nafiah, Dzuriatun (Jurnal Ilmiah Riset Aplikasi Manajemen, 2024)
Earnings management is a condition where management intervenes in the process of preparing financial reports for external parties so that they can equalize, increase and decrease profit reporting. This research aims to determine and empirically test the influence of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2022 audit quality as proxied by The Public Accountant Firm affiliated with Big Four Firm, auditor industry specialization, and auditor opinion on earnings management. This type of research is quantitative which is carried out using secondary data in the form of data from financial reports from 2020 to 2022. The sampling method in this research uses purposive sampling, so that the companies that can be sampled are 91 companies with a research year length of 3 years. The test tool used in this research is multiple linear regression. Earnings management in this research is measured using discretionary accruals. The results of this research show that the percentage influence of The Public Accountant Firm affiliated with Big Four Firm, auditor industry specialization, and auditor opinion on earnings management is 8.8%. The t test results show that partially or simultaneously audit quality as proxied by The Public Accountant Firm affiliated with Big Four Firm, auditor industry specialization, and auditor opinion have an effect on earnings management.